Molecular detection of drug resistant polymorphisms in Plasmodium falciparum isolates from Southwest, Nigeria - Monday Tola; Olumide Ajibola; Emmanuel Taiwo Idowu; Olusesan Omidiji; Samson Taiwo Awolola; Alfred Amambua-Ngwa (BMC Research Notes, 2020)
Abstract Objective Nigeria bears 25% of global malaria burden despite concerted efforts towards its control and elimination. The emergence of drug resistance to first line drugs, artemisinin combination therapies (ACTs), indicates an urgent need for continuous molecular surveillance of drug resistance especially in high burden countries where drug interventions are heavily relied on. This study describes mutations in Plasmodium falciparum genes associated with drug resistance in malaria; Pfk13, Pfmdr1, PfATPase6 and Pfcrt in isolates obtained from 83 symptomatic malaria patients collected in August 2014, aged 1–61 years old from South-west Nigeria. Results Two Pfmdr1, N86 and Y184 variants were present at a prevalence of 56% and 13.25% of isolates respectively. There was one synonymous (S679S) and two non-synonymous (M699V, S769M) mutations in the PATPase6 gene, while Pfcrt genotype (CVIET), had a prevalence of 45%. The Pfk13 C580Y mutant allele was suspected by allelic discrimination in two samples with mixed genotypes although this could not be validated with independent isolation or additional methods. Our findings call for robust molecular surveillance of antimalarial drug resistance markers in west Africa especially with increased use of antimalarial drugs as prophylaxis for Covid-19.